Study guides

☆☆

Q: What is -6n minus 9n?

Write your answer...

Submit

Still have questions?

Related questions

12m + 9n - 4 - 10m + 6n = 2m + 15n - 4

11m + 6n - 2m + 9n = 9m + 15n or 3(3m + 5n)

-6N - 7

5n+6n-2n can be solved by combining like terms. Combine 5n and 6n and -2n to get 9n.

The GCF is 3n3

n - 10 + 9n - 3 n + 9n - 10 - 3 10n - 13

n - 10 + 9n - 3 = 10n - 13

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

3(3n - 1)(n + 1)

15m + 4n - 5m + 9n = 10m + 13n

It is 6n - 11.

m2 - 4mn - 12n2 = m2 - 6mn + 2mn - 12n2 = m(m - 6n) + 2n(m - 6n) = (m + 2n)(m - 6n)

People also asked